A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipeline
By adding alkenyl silica and nylon 66 to polyphenylene ether materials, and performing melt grafting reaction and blending treatment, polyphenylene ether composite materials for high-pressure strength water supply pipelines are prepared, which solves the problem of high-pressure strength of existing materials. The problem of insufficient strength and processability under pressure has been achieved, and efficient water supply pipe material preparation has been achieved.
Patent Information
- Application Number
- CN202211049744.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-08-30
AI Technical Summary
The strength and processing performance of existing water supply pipeline materials under high pressure are insufficient, and the flow performance of polyphenylene ether materials is poor, and the processing performance and impact resistance are poor.
By mixing with ionic water, emulsifier sodium sodium sulfate, nano-sanxide, and γ-methyl acryl oxyxyxyxyxyxyxyne hybrid, obtained olene-based silicon dioxide, and polysthenylene ether , Pyornhylene, Malayside, and Discovery agents are fused with branches to form modifiers. Then mix with nylon 66, antioxidants, antibacterials, and dispersers. The dual screw extruder is mixed together to prepare a high -pressure intensity water supply pipeline composite material.
The high pressure and high intensity of polybenzenzenzenzenzenzenzenzene ether composite materials can be improved, its processing performance and mechanical properties are improved, the water supply pipelines of high pressure intensity are suitable for high -pressure intensity, and antibacterial performance is improved.
Smart Images

Figure CN115216133B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipeline. Background Art
[0002] Currently, commonly used water supply pipe materials are usually made by processing and molding synthetic resins. They have the characteristics of good corrosion resistance, non-toxicity and odorlessness. They mainly use polyvinyl chloride materials, high-density polyethylene materials, polypropylene materials, etc., and are widely used in municipal water supply and drainage, industrial water supply and drainage and other fields. However, polyvinyl chloride materials are easy to breed bacteria, and the hygienic performance is difficult to guarantee for a long time, and the pipes are brittle; high-density polyethylene is widely used in the field of plastic pipes, but its strength is relatively low; polypropylene materials are widely used in the fields of construction and indoor water supply, but their pressure-bearing capacity is general, and the pipe wall thickness needs to be thickened to withstand greater pressure. At the same time, the pipe rigidity is insufficient and the heat resistance is poor.
[0003] Polyphenylene ether is an engineering plastic with excellent comprehensive performance. It is non-toxic, has the advantages of high strength, good flame retardancy, good corrosion resistance, water resistance, heat resistance, strong creep resistance, etc., and has good hygienic performance, which meets the necessary performance of plastic pipes. However, polyphenylene ether materials have poor flow properties, poor processing performance and impact resistance. By modifying polyphenylene ether materials, the problems faced by polyphenylene ether in water supply pipes can be overcome. Chinese patent CN104059350B discloses a modified polyphenylene ether material for pipes. By adding other resins and nano-calcium carbonate and polyphenylene ether, the prepared modified polyphenylene ether material has good heat resistance and corrosion resistance, and the processing performance is improved. However, the phenomenon of uneven mixing is easy to occur in the modified polyphenylene ether material, which has a great influence on the mechanical properties and comprehensive properties of the material. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe, which solves the problem of poor processability of the polyphenylene ether composite water supply pipe and obtains a water supply pipe with high pressure resistance and high strength.
[0005] In order to achieve the above object, the present invention discloses a method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe, comprising the following steps:
[0006] Step 1: Ultrasonically mix deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane to react at a temperature of 65-80° C. for 8-12 hours. After the reaction is completed, filter and wash with deionized water and ethanol. After washing, vacuum dry in a vacuum drying oven at 55-60° C. for 6-12 hours to obtain olefinated silica;
[0007] Step 2: uniformly mix polyphenylene ether (PPO), olefinic silica, styrene, maleic anhydride and an initiator, and perform a melt grafting reaction. After the reaction is completed, the mixture is cooled to obtain a modified polyphenylene ether;
[0008] Step 3: Mix polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant, antibacterial agent and dispersant in a mixer at a speed of 550-650 rpm / min for 3-5 min. After mixing evenly, transfer to a twin-screw extruder for extrusion, granulation, drying and homogenization to obtain a polyphenylene ether composite material for water supply pipes with high pressure strength.
[0009] Preferably, in the step 1, the mass ratio of deionized water, emulsifier sodium dodecyl sulfate, nano-silicon dioxide, and γ-methacryloxypropyltrimethoxysilane is 750-1250:3-5:100:10-18.
[0010] Preferably, in step 2, the mass ratio of polyphenylene ether, olefinic silica, styrene, maleic anhydride and initiator is 100:3-7:5-18:6-24:0.5-1.2.
[0011] Preferably, the melt grafting reaction in step 2 is carried out in a torque rheometer. During the melt grafting reaction, the rotation speed is 60-75 rpm / min, the temperature of the melt grafting reaction is 225-245° C., and the time of the melt grafting reaction is 7-12 min.
[0012] Preferably, the initiator in step 2 is dicumyl peroxide.
[0013] Preferably, in step three, the mass ratio of polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant, antibacterial agent and dispersant is 100:15-35:6-20:0.1-0.4:0.8-1.5:0.4-0.8.
[0014] Preferably, the antioxidant in step three includes one of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 1098.
[0015] Preferably, the antibacterial agent in step three includes one of 8-hydroxyquinolone, polyhexamethylene biguanide, and dodecyldimethylbenzyl ammonium chloride.
[0016] Preferably, the dispersant in step three comprises one of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.
[0017] Preferably, in step 3, the speed of the screw is 250-300 rpm / min, the temperature at the head of the twin-screw extruder is 190-210°C, and the extrusion temperature is 245-265°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. In the present invention, γ-methacryloxypropyltrimethoxysilane is first used to modify nano-silica. In a deionized water solvent, under the action of an emulsifier, sodium dodecyl sulfate, alkenyl groups are introduced on the surface of the nano-silica to obtain alkenylated silica. Polyphenylene ether, alkenylated silica, styrene, maleic anhydride, and an initiator, dicumyl peroxide, are subjected to melt grafting reaction. Polyphenylene ether reacts with maleic anhydride to introduce alkenyl groups on the surface. Then, a melt grafting reaction is carried out with styrene and alkenylated silica under the action of an initiator, dicumyl peroxide, to obtain modified polyphenylene ether. After the polyphenylene ether, modified polyphenylene ether, nylon 66, an antioxidant, an antibacterial agent, and a dispersant are uniformly mixed, the mixture is melt blended in a twin-screw extruder to obtain a polyphenylene ether composite material for a high-pressure strength water supply pipeline. After the antibacterial agent is added, the antibacterial property of the polyphenylene ether composite material can be improved. When used as a material for a water supply pipeline, the composite material has an excellent antibacterial effect.
[0020] 2. The nano-silicon dioxide used in the present invention has a nano-size effect and good mechanical properties. When stretched by external force, it can make the polyphenylene ether matrix produce large-area yielding, promote the brittle-toughness transformation of the matrix, and improve the mechanical properties of the matrix. At the same time, the nano-silicon dioxide is grafted onto the polyphenylene ether by the grafting method, which effectively avoids the agglomeration of the nano-silicon dioxide, so that the nano-silicon dioxide can be evenly dispersed in the polyphenylene ether matrix. At the same time, the styrene thermoplastic plastic has excellent weather resistance, heat resistance, and compression deformation resistance, which can well improve the comprehensive performance of the polyphenylene ether matrix. The polyphenylene ether, modified polyphenylene ether and nylon 66 are blended to generate block or graft copolymers, gradually forming a continuous network structure, achieving It has the effect of increasing the volume, improving the processing performance of the polyphenylene ether matrix, and making the dispersion more uniform. At the same time, the bonding force between the dispersed phases is stronger, showing improved mechanical properties, and can better transmit stress. After blending, it can provide more stress concentration points, causing polyphenylene ether and nylon 66 to produce a large number of silver streaks and shear bands to consume energy. Since polyphenylene ether contains a large number of benzene rings on the main chain, in the category of rigid polymer chains, the addition of nylon 66 can improve this defect. Nylon 66 has a flexible long chain that can improve the rigidity of the polyphenylene ether matrix. When subjected to external force, it can absorb more external force. The polyphenylene ether composite material exhibits strong mechanical properties, and the prepared water supply pipe can adapt well to high pressure strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe in the present invention;
[0022] Figure 2It is a test graph of tensile strength and elongation at break of the polyphenylene ether composite material corresponding to samples 1-8 in the present invention;
[0023] Figure 3 This is a graph showing the impact strength test of the polyphenylene ether composite material corresponding to samples 1-8 in the present invention. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0027] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 750:3:100:10 were ultrasonically mixed and reacted at a temperature of 65° C. for 12 h. After the reaction was completed, the mixture was filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 55° C. for 12 h to obtain olefinated silica;
[0028] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:3:5:6:0.5 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 60 rpm / min, the temperature of the melt grafting reaction was 225° C., and the time of the melt grafting reaction was 12 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0029] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:15:6:0.1:0.8:0.4 were mixed in a mixer at a speed of 550 rpm / min for a mixing time of 5 min. After uniform mixing, the mixture was transferred to a twin-screw extruder for extrusion at a screw speed of 250 rpm / min, a temperature at the head of the twin-screw extruder of 190°C, and an extrusion temperature of 245°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength was obtained.
[0030] Example 2
[0031] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0032] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 900:3.5:100:12 were ultrasonically mixed and reacted at a temperature of 70° C. for 10 h. After the reaction was completed, the mixture was filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 55° C. for 10 h to obtain olefinated silica;
[0033] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:4:8:10:0.7 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 65 rpm / min, the temperature of the melt grafting reaction was 230° C., and the time of the melt grafting reaction was 8 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0034] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:20:9:0.18:1:0.5 are mixed in a mixer at a speed of 580 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 260 rpm / min, a temperature at the head of the twin-screw extruder of 195°C, and an extrusion temperature of 250°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0035] Example 3
[0036] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0037] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1050:4:100:14 were ultrasonically mixed and reacted at a temperature of 70° C. for 10 h. After the reaction was completed, the mixture was filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 55° C. for 10 h to obtain olefinated silica;
[0038] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:5:11:15:0.9 were mixed evenly, and added to a torque rheometer for melt grafting reaction. The speed of the torque rheometer during the melt grafting reaction was 68 rpm / min, the temperature of the melt grafting reaction was 235° C., and the time of the melt grafting reaction was 9 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0039] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:25:13:0.25:1.2:0.6 are mixed in a mixer at a speed of 600 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 270 rpm / min, a temperature at the head of the twin-screw extruder of 200°C, and an extrusion temperature of 255°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0040] Example 4
[0041] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0042] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0043] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0044] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 are mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205°C, and an extrusion temperature of 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0045] Example 5
[0046] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0047] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1250:5:100:18 were ultrasonically mixed and reacted at a temperature of 80° C. for 8 hours. After the reaction was completed, the mixture was filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 6 hours to obtain olefinated silica;
[0048] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:7:18:24:1.2 were mixed evenly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 75 rpm / min, the temperature of the melt grafting reaction was 245° C., and the time of the melt grafting reaction was 7 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0049] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:35:20:0.4:1.5:0.8 are mixed in a mixer at a speed of 650 rpm / min for a mixing time of 3 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 300 rpm / min, a temperature at the head of the twin-screw extruder of 210°C, and an extrusion temperature of 265°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0050] Example 6
[0051] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0052] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0053] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0054] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 168, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 were mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture was transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205°C, and an extrusion temperature of 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength was obtained.
[0055] Example 7
[0056] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0057] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0058] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0059] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1076, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 are mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205°C, and an extrusion temperature of 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0060] Example 8
[0061] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0062] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0063] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0064] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent 8-hydroxyquinolinone, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 were mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture was transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205°C, and an extrusion temperature of 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength was obtained.
[0065] Example 9
[0066] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0067] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0068] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0069] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, antibacterial agent dodecyl dimethyl benzyl ammonium chloride, and dispersant polyvinyl pyrrolidone in a mixer with a mass ratio of 100:30:16:0.35:1.4:0.7. The speed of the mixer is 620 rpm / min. The mixing time is 4 min. After mixing evenly, the mixture is transferred to a twin-screw extruder for extrusion. The speed of the screw is 285 rpm / min. The temperature at the head of the twin-screw extruder is 205°C. The extrusion temperature is 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0070] Comparative Example 1
[0071] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0072] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0073] (2) Polyphenylene ether, olefinic silica, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 are mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205°C, and an extrusion temperature of 260°C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0074] Comparative Example 2
[0075] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0076] (1) Polyphenylene ether, nano-silicon dioxide, nylon 66, antioxidant 1010, antibacterial agent polyhexamethylene biguanide, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:1.4:0.7 are mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture is transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205° C., and an extrusion temperature of 260° C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength is obtained.
[0077] Comparative Example 3
[0078] A method for preparing a polyphenylene ether composite material for a high-pressure strength water supply pipe comprises the following steps:
[0079] (1) Deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1200:4.5:100:16 are ultrasonically mixed and reacted at a temperature of 75° C. for 10 h. After the reaction is completed, the mixture is filtered, washed with deionized water and ethanol, and then vacuum dried in a vacuum drying oven at 60° C. for 10 h to obtain olefinated silica;
[0080] (2) polyphenylene ether, olefinic silica, styrene, maleic anhydride, and initiator dicumyl peroxide in a mass ratio of 100:6:15:20:1.1 were mixed uniformly, and added to a torque rheometer for melt grafting reaction. During the melt grafting reaction, the speed of the torque rheometer was 72 rpm / min, the temperature of the melt grafting reaction was 240° C., and the time of the melt grafting reaction was 10 min. After the reaction was completed, the mixture was cooled to obtain a modified polyphenylene ether;
[0081] (3) Polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant 1010, and dispersant polyvinyl pyrrolidone in a mass ratio of 100:30:16:0.35:0.7 were mixed in a mixer at a speed of 620 rpm / min for a mixing time of 4 min. After uniform mixing, the mixture was transferred to a twin-screw extruder for extrusion at a screw speed of 285 rpm / min, a temperature at the head of the twin-screw extruder of 205° C., and an extrusion temperature of 260° C. After granulation, drying, and homogenization, a polyphenylene ether composite material for water supply pipes with high pressure strength was obtained.
[0082] The nano-silicon dioxide used in the embodiments and comparative examples was provided by Jiangsu Tianxing New Materials Co., Ltd., model TSP-H10, with a particle size of 20 nm; polyphenylene ether was provided by Ruicheng Branch of Bluestar Chemical New Materials Co., Ltd., with Mn=16785 g / mol; nylon 66 was provided by Pingdingshan Shenma Material Processing Co., Ltd., model FYR2.7, with a viscosity of 2.7 Pa·s.
[0083] The mechanical properties of the polyphenylene ether composite materials for high pressure strength water supply pipes prepared in Examples 1-5 and Comparative Examples 1-3 were tested, wherein the composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were named Samples 1-8.
[0084] The tensile properties were tested according to the GB / T 1040.1-2018 test standard using a CMT4101 electronic tensile testing machine; the notched impact strength was tested according to the GB / T 1843-2008 test standard using a XIJ-5 simply supported beam impact testing machine. The test results are shown in Table 1:
[0085] Table 1 Mechanical properties test table of polyphenylene ether composite materials
[0086]
[0087] According to the test results in Table 1, the mechanical properties of samples 1-5 are significantly improved compared with those of samples 6-8, among which the tensile strength of sample 5 can reach 70.1MPa and the impact strength can reach 1079.1J / m 2; The elongation at break of sample 3 can reach 29.9%; in the composite material of sample 6, olefinic silica is added, but modified polyphenylene ether is not added, and the mechanical properties of the composite material are reduced, but compared with the direct addition of nano-silicon dioxide in sample 7, the dispersibility of silica is greatly improved, which prevents the poor mechanical properties of the polyphenylene ether composite material due to agglomeration of nano-silicon dioxide; no antibacterial agent is added in sample 8, which has little effect on the mechanical properties of the composite material; in samples 1-5, the content of modified polyphenylene ether added is increased, and nano-silicon dioxide has excellent mechanical properties, which can effectively improve the strength of polyphenylene ether and improve the compressive strength of polyphenylene ether. Nano-silicon dioxide is grafted with polyphenylene ether and polystyrene by the melt grafting method, which effectively improves the mechanical properties of polyphenylene ether and avoids the agglomeration of nano-silicon dioxide. At the same time, the modified polyphenylene ether and polyphenylene ether are mixed, which effectively improves the compatibility between polyphenylene ether and nylon 66, and the mechanical properties of the obtained composite material are more excellent.
[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe, characterized in that: The following steps are involved: Step 1: Ultrasonically mix deionized water, emulsifier sodium dodecyl sulfate, nano-silica, and γ-methacryloxypropyltrimethoxysilane to react at a temperature of 65-80° C. for 8-12 hours. After the reaction is completed, filter and wash with deionized water and ethanol. After washing, vacuum dry in a vacuum drying oven at 55-60° C. for 6-12 hours to obtain olefinated silica; Wherein, the mass ratio of deionized water, emulsifier sodium dodecyl sulfate, nano-silicon dioxide, and γ-methacryloxypropyltrimethoxysilane is 750-1250:3-5:100:10-18; Step 2: uniformly mix polyphenylene ether, olefinated silica, styrene, maleic anhydride and initiator, and perform melt grafting reaction. After the reaction is completed, cool the mixture to obtain modified polyphenylene ether; Wherein, the mass ratio of polyphenylene ether, olefinic silica, styrene, maleic anhydride and initiator is 100:3-7:5-18:6-24:0.5-1.2; Step 3: Mix polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant, antibacterial agent and dispersant in a mixer at a speed of 550-650 rpm / min for 3-5 min. After mixing evenly, transfer to a twin-screw extruder for extrusion, granulation, drying and homogenization to obtain a polyphenylene ether composite material for water supply pipes with high pressure strength; Among them, the mass ratio of polyphenylene ether, modified polyphenylene ether, nylon 66, antioxidant, antibacterial agent and dispersant is 100:15-35:6-20:0.1-0.4:0.8-1.5:0.4-0.
8.
2. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: The melt grafting reaction in step 2 is carried out in a torque rheometer. During the melt grafting reaction, the rotation speed is 60-75 rpm / min, the temperature of the melt grafting reaction is 225-245° C., and the time of the melt grafting reaction is 7-12 min.
3. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: The initiator in the step 2 is dicumyl peroxide.
4. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: The antioxidant in step three includes one of antioxidant 1010, antioxidant 168, and antioxidant 1076.
5. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: The antibacterial agent in step three includes one of 8-hydroxyquinolinone, polyhexamethylene biguanide, and dodecyl dimethyl benzyl ammonium chloride.
6. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: The dispersant in step three is polyvinyl pyrrolidone.
7. The method for preparing a polyphenylene ether composite material for a high pressure strength water supply pipe according to claim 1, characterized in that: In the step 3, the speed of the screw is 250-300 rpm / min, the temperature at the head of the twin-screw extruder is 190-210° C., and the extrusion temperature is 245-265° C.
Citation Information
Patent Citations
A modified polyphenylene ether material for pipelines and its preparation method
CN104059350B
Flame-resistant polyphenylether composition and method for preparing same
CN101735592A
High-ultraviolet-aging-resistance maleic anhydride grafted polyphenylene ether modified epoxy resin composite material for LED (Light Emitting Diode) packaging and preparation method thereof
CN105153641A